Does regulatory Impact assessment (RIA) really evaluate regulatory impact? The case of the Czech Republic - Karel Jára; Jiří Schwarz (Charles University in Prague, Institute of Economic Studies (IES), 2012)
The basic goal of Regulatory Impact Assessment (RIA) is to improve regulatory quality by ex ante selecting the best alternative using cost-benefit analysis and enabling ex post evaluation of the real impact. Both goals are achievable only when RIA is properly implemented for all potential sources of regulation, including parliamentary amendments to bills. But these are usually not subject to RIA. This paper analyzes all bills and related amendments passed in the Czech Republic in 2010 and finds that about 15% of the adopted amendments, distributed among 17 of 34 bills, alter the original impacts of the bill. The results suggest that RIAs are often inapplicable for the ex post evaluation and the best alternative identified by RIA may not be achieved.
Keywords: D78; H11; K20; L51; 330; regulatory impact assessment; policy appraisal; better regulation; legislative process